New Paradigm of Gastric Pathogenesis: The Important Role of Gastric Microbiota - Miftahussurur, Muhammad; Savitri, Camilia Metadea Aji; I'tishom, Reny; Rejeki, Purwo Sri; Rezkitha, Yudith Annisa Ayu; Yamaoka, Yoshio (The Indonesian Society for Digestive Endoscopy, 2022)
Microbiota was deemed essential as it involved in energy metabolism, nutrient absorption, intestinal immune system maturation, and pathogen protection. Gastrointestinal microbiome played essential roles in human body, such as immune response regulation, pathogen colonization, and few other diseases. The relation between gastric microbiota and host were difficult to explore for years due to unculturable microbes. Stomach with its acid production was presumed to be sterile and unfavorable for bacterial growth until the discovery of Helicobacter pylori. It dominates the stomach as it was estimated to colonize almost 50% global population. H. pylori infection was linked to the development of chronic gastritis and recognized as a definite carcinogen. There was a probability that the alteration of gastric microbiota likely influenced gastric immunobiology and possible gastric diseases. Recent studies showed that five phyla consist of Firmicutes, Bacteroidetes, Actinobacteria, Fusobacteria and Proteobacteria have been discovered in stomach mucosa which might contribute to the pathological process. In addition, genera such as Lactobacillus, Escherichia-Shigella, Lachnospiraceae, Burkholderia and Nitrospirae were considered to have a role on gastric carcinogenesis.